Case Report: SATB2-Associated Syndrome Overlapping With Clinical Mitochondrial Disease Presentation: Report of Two Cases - Zarate, Yuri A.; Vernon, Hilary J.; Bosanko, Katherine A.; Ramani, Praveen K.; Gokden, Murat; Writzl, Karin; Meznaric, Marija; Vipotnik Vesnaver, Tina; Ramakrishnaiah, Raghu; Osredkar, Damjan (Frontiers in Genetics, 2021)
SATB2-Associated Syndrome (SAS) is an autosomal dominant neurogenetic multisystemic disorder. We describe two individuals with global developmental delay and hypotonia that underwent an extensive evaluation to rule out an underlying mitochondrial disorder before their eventual diagnosis of SAS. Although the strict application of the clinical mitochondrial disease score only led to the designation of “possible” mitochondrial disorder for these two individuals, other documented abnormalities included nonspecific neuroimaging findings on MRI and MRS, decreased complex I activity on muscle biopsy for patient 2, and variation in the size and relative proportion of type muscle fibers in the muscle biopsies were aligned with mitochondrial diseases. SAS should be in the differential diagnosis of mitochondrial disorders and broad-spectrum diagnostic tests such as exome sequencing need to be considered early in the evaluation process of undiagnosed neurodevelopmental disorders.